2022
DOI: 10.2196/26033
|View full text |Cite
|
Sign up to set email alerts
|

Implementation of an mHealth App to Promote Engagement During HIV Care and Viral Load Suppression in Johannesburg, South Africa (iThemba Life): Pilot Technical Feasibility and Acceptability Study

Abstract: Background South Africa has the largest HIV treatment program worldwide. Retention in care and medication adherence remain problematic necessitating innovative solutions for improving HIV care. The increasing availability and use of mobile technology can support positive clinical outcomes for persons living with HIV. iThemba Life is a mobile health app designed with input from South African health professionals and patients, promoting engagement with HIV care through access to medical results. … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 20 publications
2
3
0
Order By: Relevance
“…Furthermore, in nearly all the cases where phone sharing occurred, the phone was being shared with a romantic partner or family member and the phone was with the owner for most of the day. These findings are consistent with the literature on phone sharing patterns in similar populations [ 35 - 37 ]. Limited phone sharing is encouraging for mHealth interventions because it minimizes periods of loss of engagement with the intervention, as well minimizing opportunities for privacy and confidentiality loss.…”
Section: Discussionsupporting
confidence: 93%
“…Furthermore, in nearly all the cases where phone sharing occurred, the phone was being shared with a romantic partner or family member and the phone was with the owner for most of the day. These findings are consistent with the literature on phone sharing patterns in similar populations [ 35 - 37 ]. Limited phone sharing is encouraging for mHealth interventions because it minimizes periods of loss of engagement with the intervention, as well minimizing opportunities for privacy and confidentiality loss.…”
Section: Discussionsupporting
confidence: 93%
“…The proportion of phone sharing reported at follow-up (15%) is consistent with that reported at the time of enrollment (14%). This frequency of sharing is similar to another recent mHealth study in South Africa that found 11% phone sharing [ 33 ]. The possibility of phone sharing and potential lack of confidentiality should be considered when designing future mHealth studies in this setting.…”
Section: Discussionsupporting
confidence: 89%
“…Screening for our study is described elsewhere [ 31 ] and did not encounter similar challenges, but the implementation of our study did encounter similar issues with the lack of data, and inadequate RAM may have caused the installation challenges we experienced, as apps and photos sometimes needed to be deleted to make space for the CareConekta app. A different South African study from 2019 found that 13% of the eligible participants were unable to download the study app on their Android-based phone, 6% were unable to scan a barcode, and 3% were unable to complete app registration [ 33 ]. During implementation, the authors noted reports of a lack of data access and lost or broken phones.…”
Section: Discussionmentioning
confidence: 99%
“… 32 A good example is the iThemba Life application that showed that patients received HIV viral load results 10 times sooner than the standard of care. 33 Similarly, the miLINC suite of smartphone applications was designed to improve the time from diagnosis to treatment initiation for patients with rifampicin-resistant TB. 34 This study showed that the time from presentation to treatment initiation could be significantly improved by using an integrated approach.…”
Section: Discussionmentioning
confidence: 99%